The proliferation of MDA-MB-231 cells is repressed by mesenchymal stem cell-mediated macrophage activation conditioned medium through the inhibition of AKT1 and YKL-39 genes - Nur Ramziahrazanah Jumat; Muhammad Amir Yunus; Badrul Hisham Yahaya; Mohd Yusmaidie Aziz; Mohd Salleh Rofiee; Rafeezul Mohamed (ResearchGate, 2024)
Background: Triple-negative breast cancer (TNBC) is characterized by a substantial presence of tumor-associated macrophages (TAMs) exhibiting an M2-like phenotype, which plays a crucial role in promoting tumor cell stemness and invasiveness. Mesenchymal stem cells (MSCs) have the ability to induce the transformation of naive macrophages (M0) into M1-like macrophages. This study delves into the interplay between MSCs and macrophages within the context of breast cancer (BC) progression using a TNBC cell line, as reprogramming of TAMs into M1-like macrophages may emerge as a promising therapeutic strategy for BC. Methods: THP-1 cells were induced into M0 macrophages and co-cultured with UC-MSCs, subsequently analyzing CM for M1- and M2-type macrophage-related cytokines. Total RNA from co-cultured cells was used to assess IRF-4 and IRF-5 mRNA gene expression via qRT-PCR. MDA-MB-231 cells were exposed to CM and co-cultured cells to evaluate cell viability through MTT assay over 24, 48, and 72 hours, with qRT-PCR used to examine breast cancer-related gene expression. Results: The results indicate that co-culturing M0 macrophages with MSCs promotes M1-like macrophages, as evidenced by upregulated IRF-5 and suppressed M2 macrophage-related genes. Treatment with CM from M0/MSCs co-culture significantly inhibits MDA-MB-231 cell proliferation at 72 hours, accompanied by reduced TNF-α levels. Notably, CM treatment downregulates AKT1 and YKL-39 genes in MDA-MB-231 cells, suggesting potential anti-cancer effects. Direct co-culture with M0/MSCs, however, shows no significant impact on TNBC cell growth. Conclusion: This study highlights MSCs' ability to induce M0 macrophages to a M1-like phenotype and suggests that CM from M0/MSCs co-culture may contain anti-cancer factors targeting AKT1 and YKL-39 genes, underscoring the potential of MSC-mediated macrophage activation as a strategy to enhance BC treatment, especially in the context of TNBC